METAZOAN PARASITES AND OTHER EPIBIONT IN THE PLEASURE OYSTER CRASSOSTREA CORTEZIENSIS (HERTLEIN, 1951) IN TWO COASTAL ZONES OF THE MEXICAN PACIFIC - Tejeda-Arenas, Denisse (2021)
The objective of this study was to determine the presence of metazoan parasites and epibionts in the pleasure oyster Crassostrea corteziensis (Hertlein) inhabiting two coastal and fishing localities in the Mexican Pacific state of Sinaloa. 30 oysters were collected in the fishing cooperative of Playa Norte in the bay of Mazatlán, Sinaloa and a comparison made with the presence of parasites in oysters in the "Ceuta"coastal lagoon. Inspection of oysters in the coastal lagoon revealed the presence of 36 encapsulated metacercariae of the Acanthocolpidae family in the gonad of the oyster Crassostrea corteziensis. Six metacercariae were found in the Mazatlán bay Playa Norte area: three of sp. 1 (Family Hemiuridae) in the mantle, a specimen of sp. 2 (Family Fellodistomidae) in the digestive gland and a metacercaria sp3. unidentified in the mantle and a metacercaria (Family Zoogonidae) in the digestive gland; two free-living nematodes of the genus Theristus sp. As epibiont organisms, seven specimens of polychaetes of the Nereididae family were found in the shell of oysters. This work reports for the first time the invasion of the digenean Stephanostomum sp Looss, 1899 of the family Acanthocolpidae, a parasite of the gonad of the oyster Crassostrea corteziensis in the Mexican Pacific, as well as the presence of digeneans belonging to the Fellodistomidae, Hemiuridae and Zoogoniade families. The results of this work contribute to the knowledge on the biology, biodiversity and host preference of these parasites, with possible implications in the health risks posed by human consumption of the pleasure oyster, with great regionalization in the consumption of shellfish raw foods that have a broad gastronomic social identity in these coastal areas in the Mexican Pacific.